2014
DOI: 10.1007/s11356-014-3303-z
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic treatability of liquid residue from wet oxidation of sewage sludge

Abstract: Wet Oxidation (WO) of sewage sludge is a chemical oxidation of sludge at high temperatures and pressures by means of an oxygen-containing gas. The liquid stream originated by WO is easily biodegradable, and therefore, the recirculation to the biological Waste Water Treatment Plant (WWTP) may be a feasible solution. However, the WO effluent has a residual organic and nitrogen content so that its treatment may be required when the receiving WWTP has no surplus treatment capacity left. The aim of this research wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In order to reduce the energy requirements of the WO process, anaerobic digestion of the liquid residue (rich in biodegradable COD) was proposed and tested by Bertanza et al (2014b).…”
Section: Methodsmentioning
confidence: 99%
“…In order to reduce the energy requirements of the WO process, anaerobic digestion of the liquid residue (rich in biodegradable COD) was proposed and tested by Bertanza et al (2014b).…”
Section: Methodsmentioning
confidence: 99%
“…Although the research effort on hydrothermal treatments of sludge has been substantial, these works have mainly focused on VSS, COD or TOC reductions, but none of them have attempted to characterize the reaction products, even though this information will be critical to the design of subsequent techniques of purification or revalorisation of the hydrolyzed and oxidized effluent. 20 Therefore, the aim of this work was to analyze the effect of WO on the main species of polymeric substances from activated sludge. To this end, the sludge was separated into its components (SMP, LB-EPS, TB-EPS and naked cells) in order to check the differences during treatment according to the origin of the biopolymers (extracellular or intracellular), and each was subjected to WO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, the impact of WO on polymeric substances from sludge is still unknown. Although the research effort on hydrothermal treatments of sludge has been substantial, these works have mainly focused on VSS, COD or TOC reductions, but none of them have attempted to characterize the reaction products, even though this information will be critical to the design of subsequent techniques of purification or revalorisation of the hydrolyzed and oxidized effluent . Therefore, the aim of this work was to analyze the effect of WO on the main species of polymeric substances from activated sludge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the WO effluent can be conveniently treated in a conventional wastewater treatment plant because of its high biodegradability, and, in some cases, it could also be used as a carbon source for the denitrification process, and as a substrate for the production of biopolymers [12]. Moreover, other researchers have also demonstrated that WO effluent represents an interesting energy vector; in fact, if it is treated by anaerobic digestion, biogas can be produced, and electric and thermal energy could be recovered [13].Today, about 200 plants are in operation around the world (two of them in Italy), mostly to treat waste streams from petrochemical, chemical, and pharmaceutical industries, as well as residual sludge from urban wastewater treatment [12]. Detailed reviews about the WO process and its application are reported in Debellefontaine and Foussard [8], and Bhargava et al [14].According to Italian regulations [15], the soil and stones not containing dangerous substances (classified using the European Waste Code 17 05 04 [16]) can be recovered, in simplified procedure, for the following uses: ceramic and brick manufacturing processes, environmental recovery, road embankments, and foundations.…”
mentioning
confidence: 99%
“…In addition, the WO effluent can be conveniently treated in a conventional wastewater treatment plant because of its high biodegradability, and, in some cases, it could also be used as a carbon source for the denitrification process, and as a substrate for the production of biopolymers [12]. Moreover, other researchers have also demonstrated that WO effluent represents an interesting energy vector; in fact, if it is treated by anaerobic digestion, biogas can be produced, and electric and thermal energy could be recovered [13].…”
mentioning
confidence: 99%